Immunoprophylactic Potential of a New Recombinant Leishmania infantum Antigen for Canine Visceral Leishmaniasis: An In Vitro Finding - Pessoa-e-Silva, Rômulo; Trajano-Silva, Lays Adrianne Mendonça; Vaitkevicius-Antão, Victor; Santos, Wagner José Tenório dos; Magalhães, Franklin Barbalho; Moura, Danielle Maria Nascimento; Nakasone, Eiji Kevin Nakasone; de Lorena, Virgínia Maria Barros; de Paiva-Cavalcanti, Milena (Frontiers in Immunology, 2021)
The development and application of safe and effective immunoprophylactic/ immunotherapeutic agents against canine visceral leishmaniasis (CanL) have been pointed out as the only means for the real control of the disease. Thus, this study aimed to evaluate the in vitro cellular immune response of dogs, elicited by the new recombinant proteins of Leishmania infantum, Lci10 and Lci13, in order to investigate their potential for vaccinology. Twenty-four dogs were submitted to clinical, parasitological, serological and molecular tests, and then separated into two study groups: 12 infected (InD) and 12 non-infected dogs (NInD), and six of each group were directed for Lci10 and Lci13 evaluation. Peripheral blood mononuclear cells (PBMC) were cultured and stimulated with Lci10 (10 μg/ml) or Lci13 (5 μg/ml), and with L. infantum soluble antigen (LSA) (25 μg/ml) or no stimulus (NS) as controls. Afterwards, the mRNA levels of different cytokines were quantified through qPCR, and Nitric Oxide (NO) production was assessed in the culture supernatants. Significant differences were considered when p≤0.05. The comparative analysis revealed that, in the NInD group, Lci13 promoted a significant increase in the expression of IFN-γ in relation to LSA (p = 0.0362), and the expression of this cytokine in NInD was significantly higher than that presented in the InD (p = 0.0028). A negative expression for TGF-β was obtained in both groups. Lci13 also induced a greater production of NO in relation to the NS sample in the NInD group. No significant differences were observed after stimulation with Lci10. In conclusion, the results suggest a protective role of Lci13 for uninfected animals, thus with a potential for immunoprophylaxis. The results will help to direct the antigen Lci13 for further studies (pre-clinical trials), in order to determine its immunogenicity and reactogenicity effects, as a way to consolidate its real applicability for vaccinology against CanL.